2012
DOI: 10.1016/j.farma.2011.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Intervención farmacéutica al alta hospitalaria para reforzar la comprensión y cumplimiento del tratamiento farmacológico

Abstract: The pharmacist's intervention upon discharge has helped increase the percentage of patients that understood and took their medication correctly in accordance with their prescription. The number of hospital readmissions in the intervention group has also reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…15,33 Detecting these differences is crucial to customize the interventions according to each group of patients, such as adapting the information delivery materials or establishing the visits frequency. 33,35 In concordance with previous research, health professionals are situated as the preferred source of information. 11,12,15 In younger populations, a greater use of Internet was observed for health-related information search.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…15,33 Detecting these differences is crucial to customize the interventions according to each group of patients, such as adapting the information delivery materials or establishing the visits frequency. 33,35 In concordance with previous research, health professionals are situated as the preferred source of information. 11,12,15 In younger populations, a greater use of Internet was observed for health-related information search.…”
supporting
confidence: 72%
“…15,18,33,34 Therefore, it becomes important for health professionals to spend more time instructing the elderly, due to their age-specific difficulties in understanding. 35 As mentioned above, no significant…”
Section: Discussionmentioning
confidence: 80%
“…Only articles published in English were assessed for this review. Potentially, there may have been studies, such as that by Sánchez Ulayar et al , 66 published in non-English journals, involving interventions for improving care transitions. In addition, research disseminated through the grey literature, such as conference papers and unpublished reports, was not considered.…”
Section: Discussionmentioning
confidence: 99%
“…The results of several studies suggest that medication counseling before hospital discharge reduces the incidence of patient medication discrepancies and adverse drug events 4 , 7 . Counseling also improves adherence 14 , 15 , decreases readmission rates 1 , 16 and mortality 5 , and consequently results in cost savings 17 , 18 ; however, other reports have suggested that counseling has little or no effect 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%